1997
DOI: 10.1038/sj.bmt.1700630
|View full text |Cite
|
Sign up to set email alerts
|

Clinical strategies for the management of cytomegalovirus infection and disease in allogeneic bone marrow transplant

Abstract: Summary:agents have been employed in an attempt to prevent the development of CMV infection and disease where either donor or recipient are seropositive. Four clinical strategies are proposed for the management of CMV disease: prophylaxis, suppression, preThere are four therapeutic approaches which can be used. These are: emptive therapy and treatment. The degree of risk of developing CMV disease and the safety profile of the Prophylaxis: Antiviral agents are administered to all BMT presently available drugs n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 3 publications
1
34
0
3
Order By: Relevance
“…The rate of asymptomatic CMV viremia may have been underestimated, since weekly CMV DNA detection in blood was performed only after the 10th patient was enrolled in this protocol. There is currently insufficient evidence to recommend a prophylaxis strategy vs a pre-emptive monitoring strategy in these patients, 18,19 but this high rate of CMV viremia suggests that one of these two strategies should be employed. The lower incidence of invasive CMV disease compared with past literature in unprophylaxed alloBMT recipients suggests that the biology and timetable of occurrence of infection in this nonmyeloablative group may be somewhat different from recipients of 'conventional' alloBMT.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of asymptomatic CMV viremia may have been underestimated, since weekly CMV DNA detection in blood was performed only after the 10th patient was enrolled in this protocol. There is currently insufficient evidence to recommend a prophylaxis strategy vs a pre-emptive monitoring strategy in these patients, 18,19 but this high rate of CMV viremia suggests that one of these two strategies should be employed. The lower incidence of invasive CMV disease compared with past literature in unprophylaxed alloBMT recipients suggests that the biology and timetable of occurrence of infection in this nonmyeloablative group may be somewhat different from recipients of 'conventional' alloBMT.…”
Section: Discussionmentioning
confidence: 99%
“…1 The mortality of CMV diseases, particularly CMV pneumonitis, remains high even after the introduction of combined therapy with ganciclovir and immunoglobulin. 2,3 Several studies have shown that the prophylactic use of ganciclovir successfully prevented CMV diseases, but survival benefit of this approach has not been clearly demonstrated because of its toxicities, particularly neutropenia. [4][5][6] In addition, the prophylactic use of ganciclovir has been associated with increased incidence of late CMV diseases.…”
mentioning
confidence: 99%
“…Nineteen of the 28 patients with CMV viremia received AG-guided preemptive ganciclovir therapy; had the positivity of the plasma PCR assay triggered the initiation of preemptive therapy, 9 additional patients would have been unnecessarily treated since none of them developed CMV end-stage organ disease. Although the AMPLICOR CMV assay is more sensitive than AG, the latter appears to be more suitable both for guiding the initiation of preemptive therapy and for monitoring a patient's response to antiviral therapy.Cytomegalovirus (CMV) infection remains a significant cause of morbidity and mortality in allogeneic stem cell or bone marrow transplant recipients (23,24). The prevention of CMV end-stage organ disease is therefore a major goal in the clinical management of these patients.…”
mentioning
confidence: 99%
“…Cytomegalovirus (CMV) infection remains a significant cause of morbidity and mortality in allogeneic stem cell or bone marrow transplant recipients (23,24). The prevention of CMV end-stage organ disease is therefore a major goal in the clinical management of these patients.…”
mentioning
confidence: 99%